Sistem Informasi Daftar Kunjungan Berbasis Web di Kementerian Agama Kabupaten Deli Serdang - Nugroho, Agung; Rahmadani, Noni Fauzia (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
Manual recording of visit lists at the Ministry of Religious Affairs of Deli Serdang Regency faces challenges such as the risk of damage to guest books, archive accumulation, and difficulties in periodic recapitulation, which hinder effective data management and decision-making. To address these issues and support the implementation of the smart government concept, this research aims to develop a modern and efficient web-based visit list information system. Using the Research and Development (R&D) method and the waterfall software development model, the system was built through stages of requirements analysis, design, implementation, testing, and maintenance. The system includes two main interfaces: an admin section for visitor data management, recapitulation creation, Excel data export, and statistical visualization; and a user section for visit form submission and proof of registration. Built with PHP, Bootstrap, and MySQL, the system ensures a user-friendly interface and structured database. The application was tested using black-box testing to evaluate functionality and usability. Visitors successfully registered, with accurate proof of registration generated. Admin features, such as data management, recapitulation, and Excel export, operated effectively, while statistical visualizations provided actionable insights. The system demonstrated high performance, with fast response times and secure data management without loss or corruption. Usability testing revealed positive feedback, with users highlighting the intuitive interface and responsive design across devices. These results confirm the system’s ability to improve administrative efficiency, replace manual processes, and enhance transparency and accountability in public service delivery.